A Prospective Evaluation of Two Rapid Phenotypical Antimicrobial Susceptibility Technologies for the Diagnostic Stewardship of Sepsis. (10th May 2018) - Giordano, Cesira; Piccoli, Elena; Brucculeri, Veronica; Barnini, Simona
Abstract : Rapid identification of bloodstream pathogens by MALDI-TOF MS and the recently introduced rapid antimicrobial susceptibility testing (rAST) directly from positive blood cultures allow clinicians to promptly achieve a targeted therapy, especially for multidrug resistant microorganisms. In the present study, we propose a comparison between phenotypical rASTs performed in light-scattering technology (Alfred 60AST, Alifax®) and fluorescence in situ hybridization (Pheno™, Accelerate) directly from positive blood cultures, providing results in 4–7 hours. Blood samples from 67 patients admitted to the Azienda Ospedaliero-Universitaria Pisana were analyzed. After the direct MALDI-TOF MS identification, the rAST was performed at the same time both on Alfred 60AST and Pheno. Alfred 60AST provided qualitative results, interpreted in terms of clinical categories (SIR). Pheno provided identification and MIC values for each antibiotic tested. Results were compared to the broth microdilution assay (SensiTitre™, Thermo Fisher Scientific), according to EUCAST rules. Using Alfred 60AST, an agreement was reached, 91.1% for Gram-negative and 95.7% for Gram-positive bacteria, while using Pheno, the agreement was 90.6% for Gram-negative and 100% for Gram-positive bacteria. Both methods provided reliable results; Alfred 60AST combined with MALDI-TOF MS proved itself faster and cheaper. Pheno provided identification and MIC determination in a single test and, although more expensive, may be useful whenever MIC value is necessary and where MALDI-TOF MS is not present.